(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Teaching English for academic purposes in non-English speaking countries involves many challenges and opportunities. Since English is considered the main medium of Global Communication, Science, Technology and education, learning this language is essential for students to succeed in the academic field. However, the process of teaching English in a non-native language setting has its own complex sides, which is very important to consider the possibility of identifying and overcoming the problems that arise in this process.